Employee Perception Of The Performance Appraisal Justice And Its Relationship With Employee Engagement And Affective Commitment - Abdul Hamid, Hazlan (2017)
The main objective of this study was to investigate the employees' perceived performance appraisal justice, which is based on the Malaysian Performance Appraisal System for the civil servants, that might influence the engagement and commitment of the employees. Underpinned by the Social Exchange Theory, Equity Theory, and the Job Demands-Resources Model, this study examined the relationships between the perceived performance appraisal justice and affective commitment that was mediated by job engagement and organisation engagement. Using stratified and judgmental sampling techniques, 366 respondents comprising the non-academic employees were selected from USM as the study sample. A cross-sectional survey was employed to collect the data. Only 252 usable data were subject to hypotheses testing using the partial least squares structural equation modeling. Results showed that: (a) performance appraisal distributive justice is positively related to job engagement; (b) performance appraisal distributive justice is positively related to organisation engagement; (c) job engagement is positively related to affective commitment; (d) organisation engagement is positively related to affective commitment; and (e) performance appraisal procedural justice is positively related to affective commitment. Results also showed that organisation engagement fully mediated the relationship between performance appraisal distributive justice and affective commitment. Theoretically, this study contributes to the existing literature by providing support for the importance of job and organisation engagement as a mean to explaining the relationship between perceived performance appraisal justice and affective commitment. Practically, this present study provides insights for USM to improve policies and cultivate the justice culture in governing the performance appraisal system, to engage the employees in their job and organisation as well as to nurture employees' positive emotional attachment to the organisation.